2015
DOI: 10.1007/s12325-015-0254-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Saline in Conjunction with High-Dose Furosemide Improves Dose–Response Curves in Worsening Refractory Congestive Heart Failure

Abstract: IntroductionDiuretic responsiveness in patients with chronic heart failure (CHF) is better assessed by urine production per unit diuretic dose than by the absolute urine output or diuretic dose. Diuretic resistance arises over time when the plateau rate of sodium and water excretion is reached prior to optimal fluid elimination and may be overcome when hypertonic saline solution (HSS) is added to high doses of furosemide.MethodsForty-two consecutively hospitalized patients with refractory CHF were randomized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
(26 reference statements)
0
17
0
3
Order By: Relevance
“… 37 Administration of hypertonic saline has been shown to increase intraluminal furosemide concentrations as well as to increase 24 h of diuresis, urinary sodium levels, and urinary osmolarity. 39 Another aspect of reduced renal blood flow is the overactivation of the tubuloglomerular feedback mechanism, which may be defined as a vasomotor response to tubular osmolarity and sodium concentrations detected by macula densa cells. 40 Correction of such a compensatory feedback mechanism by means of hypertonic saline treatment and many other drugs, such as mannitol and dextran, that may attract extravascular volume towards intravascular compartments has been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 Administration of hypertonic saline has been shown to increase intraluminal furosemide concentrations as well as to increase 24 h of diuresis, urinary sodium levels, and urinary osmolarity. 39 Another aspect of reduced renal blood flow is the overactivation of the tubuloglomerular feedback mechanism, which may be defined as a vasomotor response to tubular osmolarity and sodium concentrations detected by macula densa cells. 40 Correction of such a compensatory feedback mechanism by means of hypertonic saline treatment and many other drugs, such as mannitol and dextran, that may attract extravascular volume towards intravascular compartments has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Both exert their cardiac effect by activating cell surface‐associated particulate guanylate cyclase A, which in turn increases the concentration of cGMP in the subsarcolemmal compartment. 39 , 40 The myocardial response to acute stretch represents a fundamental adaptive capacity of the heart. Nevertheless, our findings concerning a lower degree of increase in inflammatory and myocardial stretching markers after an acute saline load could suggest a possible modulatory role of HSS plus a moderate/high dose of furosemide in subjects with HFrEF.…”
Section: Discussionmentioning
confidence: 99%
“…In the genesis of hypervolemic hyponatremia, i.e., the one that typically occurs during CHF or liver cirrhosis, a frequent overlap of iatrogenic causes has been demonstrated, primarily consisting of overzealous or excessive use of drastic diuretic therapies, capable of worsening the state of reduced arterial effective circulating volume so as to elicit further secretion of ADH. The generation of a state of relative intravascular volume depletion may be prevented using albumin [ 29 ] or hypertonic saline solution [ 30 ], capable of preserving an adequate vascular refilling rate, subsequently to the depletion of the circulating volume arising from the adoption of high doses of IV loop diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an increasing number of studies have recently described an enhanced pharmacological efficacy of furosemide when administered with HSS in HF [53]. Specifically, in 2015 Paterna et al [54] reported the dose-response curve following the intravenous administration of high doses of furosemide diluted in HSS. They observed a significant improvement of both urinary output and sodium excretion rate, corresponding to a shift in the dose-response curve to the left.…”
Section: Strategies To Overcome Diuretic Resistancementioning
confidence: 99%